PERAN MEDIA SOSIAL DALAM PENINGKATAN PENJUALAN JASA LAUNDRY (STUDY KASUS PADA QUEEN LAUNDRY) - Riska Dewi Susanti; Mrihrahayu Rumaningsih; Zandra Dwanita Widodo (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purposes of this study were: 1) To measure and test the effect of both partially and simultaneously social media Whatsapp, Facebook, and Instagram on increasing sales. 2) To find out the variables that have the most dominant influence on increasing sales of laundry services at Queen Laundry Solo. This research was conducted by taking the research location at Queen Laundry Solo, while the object of this research was customers who had used Queen laundry services. Considering that the arrival of consumers cannot be known, so that the distribution of the population is unknown, according to Cooper and Schindler the number of samples taken is 96 consumers. The results of the study found that both partially and simultaneously social media Whatsapp, Facebook, and Instagram had a positive and significant effect on increasing sales at Queen Laundry Solo. It is also known that social media through Whatsapp has the most dominant influence on increasing sales. The increase in sales at Queen Laundry can be explained by social media Whatsapp, Facebook, and Instagram by 79.70% and the remaining 20.30% is explained by other variables outside the variables studied in this study.